CALL Communities and Culture – Short Papers From EUROCALL 2016 2016
DOI: 10.14705/rpnet.2016.eurocall2016.612
|View full text |Cite
|
Sign up to set email alerts
|

Flip-J: development of the system for flipped jigsaw supported language learning

Abstract: This study aims to develop and evaluate a language learning system supported by the 'flipped jigsaw' technique, called 'Flip-J'. This system mainly consists of three functions: (1) the creation of a learning material database, (2) allocation of learning materials, and (3) formation of an expert and jigsaw group. Flip-J was developed as the plugin of the learning management system Moodle, and the formative evaluation for its improvement was conducted in a language learning class. Learners were required to answe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
1
0
0
Order By: Relevance
“…Referring the results of quantitative analysis showed that the flipped classroom modified by integrating with jigsaw IV as an instructional model is considered as more effective since it resulted better achievement in the post-test than pre-test. This finding was in line with other scholars' findings which have found that the flipped classroom model was combined with other cooperative learning techniques resulted better performance on students' learning achievement [16] [17] [18].…”
Section: Resultssupporting
confidence: 92%
“…Referring the results of quantitative analysis showed that the flipped classroom modified by integrating with jigsaw IV as an instructional model is considered as more effective since it resulted better achievement in the post-test than pre-test. This finding was in line with other scholars' findings which have found that the flipped classroom model was combined with other cooperative learning techniques resulted better performance on students' learning achievement [16] [17] [18].…”
Section: Resultssupporting
confidence: 92%